IDENTIFIKASI KELAYAKAN INFRASTRUKTUR TEMPAT PENAMPUNGAN SAMPAH (TPS) DI KOTA PALEMBANG - Denny Adlan; Fajar Sadik Islami; Chanel Tri Handoko; Susi Susanti (LATERAL: Jurnal Teknik Sipil, 2023)
Containerization, collection, transportation, and final processing form the basis of the waste management system. These systems all require effective integration. Containment is a crucial basic component of waste management that is carried on to the collection system. An appropriate infrastructure is needed to support this system. Temporary waste storage areas with storage tank amenities are known as trash bins or TPS. The feasibility of TPS infrastructure is discussed in this study starting with the current state, the kind of damage that happened, and suggestions for improving the feasibility findings. The field observations, observations, and references for the TPS eligibility requirements, including SNI 19-2454-2002 and Minister of Public Works Regulation Number 03/PRT/M/2013, were employed as the data collection approaches. The garbage sorting criteria have not been met, according to the identification results, but the waste collection time conditions have been met because there is already a collection and transportation schedule, to not exceed 24 hours.